2008
DOI: 10.1111/j.1365-2664.2007.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

The untamed shrew: on the termination of an eradication programme for an introduced species

Abstract: Summary 1.One option in managing introductions of non-native pest species is to eradicate the introduced species by trapping or otherwise removing individuals. A central issue in undertaking such a programme is deciding when it is reasonable to terminate the programme because all individuals have been removed. This decision requires knowledge of the probability that complete eradication has been achieved.2. An objective Bayesian method is presented to determine the probability that all individuals of an introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…Detecting the final few individuals and/or demonstrating that there are no more individuals remaining are arguably the hardest parts of any eradication program. Thus developing techniques that allow eradication declaration without the reliance solely on the lack of physical observation is now a research focus for biotic invasions (Solow et al 2008;Rivadeneira et al 2009;Rout et al 2009). Prior personal experience with this species has already shown that small persisting populations are easily detected 2-3 month post-treatment, thereby allowing a sole reliance on visual assessment.…”
Section: Discussionmentioning
confidence: 98%
“…Detecting the final few individuals and/or demonstrating that there are no more individuals remaining are arguably the hardest parts of any eradication program. Thus developing techniques that allow eradication declaration without the reliance solely on the lack of physical observation is now a research focus for biotic invasions (Solow et al 2008;Rivadeneira et al 2009;Rout et al 2009). Prior personal experience with this species has already shown that small persisting populations are easily detected 2-3 month post-treatment, thereby allowing a sole reliance on visual assessment.…”
Section: Discussionmentioning
confidence: 98%
“…If available data are more detailed than a presence–absence record, then methods that make use of this additional information (e.g. Solow et al . 2008) would be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…These issues highlight the need for careful consideration of the assumptions underlying these methods, and the value of conducting simulations to experimentally test how robust the methods are to assumption violations. For example, these statistical methods may not be appropriate for evaluating eradiation programs as the sightings (e.g., trap captures) are not independent of the decline (see Solow et al, 2008 for an alternative method). While others (Burgman et al, 1995;McCarthy, 1998) have attempted to resolve questions over sighting effort, more work is needed in this area.…”
Section: Uniform Ppcc Field Significance Testmentioning
confidence: 99%